Loss of E-cadherin and Acquisition of Vimentin in Epithelial-Mesenchymal Transition are Noble Indicators of Uterine Cervix Cancer Progression - Myong, Na-Hye (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2012)
BACKGROUND: Epithelial-mesenchymal transition (EMT) has been known to play a key role in the stromal invasion of carcinoma in situ (CIS) lesion. Loss of E-cadherin and acquisition of vimentin are two critical steps in EMT, that are induced by Snail-1 upregulation associated with overexpression of epidermal growth factor receptor (EGFR). However, roles of EMT-related proteins in human cervical tissues have not been fully elucidated. In this study, we investigated the immunoexpressions of EMT-related proteins in CIS, microinvasive squamous cell carcinoma (SCC), and invasive SCC to demonstrate their key roles in tumor progression. METHODS: Eighty one CIS, 17 microinvasive, and 21 invasive SCC cases were immunostained with primary antibodies for Snail-1, EGFR, E-cadherin, and vimentin on paraffin-embedded tissue microarray blocks. RESULTS: EGFR and Snail-1 proteins were highly expressed but the levels were not significantly different between the three groups. However, loss of E-cadherin and acquisition of vimentin were proven to occur significantly higher in microinvasive and invasive SCC cases than in CIS. CONCLUSIONS: E-cadherin and vimentin were found to be two useful indicators of EMT in evaluating stromal invasion of CIS. However, it was not demonstrated for Snail-1 and EGFR proteins to play any key role in the progression of cervix cancer.